Příprava realizace bytového domu ve Zlíně - Saňák, Adam (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Diplomová práce se zabývá organizací výstavby bytového domu ve Zlíně. Obsahuje technologické předpisy pro piloty a monolitické konstrukce, návrh strojní sestavy, zajištění kvalitativních požadavků, časové plánování výstavby a organizaci výstavby.

Diploma thesis contains descriptions of technological process of Residential House in Zlín. The project includes a technical report for pills and monolithic constructions, mechanization plans, safety and guality of work, report scheduling and organization of construction.
CONSTRUCTION AND TECHNOLOGICAL PROJECT OF RESIDENTIAL BUILDING IN ZLIN
Keywords: Bytový dům; zařízení staveniště; vrtané piloty; CFA piloty; jeřáb; strojní sestava; časový plán; bezpečnost práce; kontrolní a zkušební plán; Residential building; site equipment; drilled pile; CFA pilling; crane; technical report; schedule; safety; control and test plan